Group Prenatal Care and Maternal Outcomes: A Scoping Review. Issue 6 (November 2021) - Tucker, Curisa M.; Felder, Tisha M.; Dail, Robin B.; Lyndon, Audrey; Allen, Kari-Claudia
Abstract: Purpose: The objective of this study was to examine the current state of literature on group prenatal care and its impact on maternal outcomes and racial disparities in adverse maternal outcomes. Design: We conducted a scoping review of literature published between January 2010 and December 2020 using the PRISMA-ScR reporting checklist. Methods: Eligible studies were identified using key words and MeSH terms in PubMed, CINAHL, and Web of Science. Inclusion criteria were studies that were (a) conducted in the United States; (b) published between January 2010 and December 2020; (c) in English; (d) focused on the primary investigation of group prenatal care and reporting on maternal comorbidity outcomes; and (e) an observational study or clinical trial. Results: Nine studies met inclusion criteria. They reported on outcomes of preeclampsia, gestational hypertension, gestational diabetes mellitus, final A1C among patients with gestational diabetes mellitus, and postpartum hemorrhage. None reported on racial disparities for minoritized populations. Among all reported maternal outcomes, results were mixed, providing inconclusive evidence. Clinical Implications: Outcomes from group prenatal care focus more on neonatal outcomes than maternal outcomes. More studies are needed with stronger designs. Given pervasive racial disparities in U.S. maternal mortality, future studies should assess how group prenatal care participation may contribute to fewer experiences of racial discrimination and implicit bias for Black women in maternity care. Abstract : Group prenatal care has potential to enhance pregnancy outcomes, however the focus of most studies of group prenatal care has been on neonatal outcomes. Little is known about the effect of group prenatal care on maternal outcomes. In this scoping review, results of studies comparing group prenatal care with traditional one-on-one prenatal care are analyzed, gaps in the literature are identified, and recommendations for research are offered.